Student-Centered Learning in Scientific Writing Training to Enhance the Academic Literacy of Senior High School Students: A Systematic Literature Review - Saeful Hamdi (Formad English Foundation NTB-Jakarta, 2026)
The increasing demand for twenty-first-century competencies has highlighted the importance of scientific writing and academic literacy as essential skills for senior high school students. However, conventional teacher-centered instruction often provides limited opportunities for students to actively construct knowledge and develop scientific communication skills. This study aimed to synthesize recent empirical evidence on how Student-Centered Learning (SCL) contributes to scientific writing training in enhancing students' academic literacy and to identify the most effective pedagogical strategies reported in the literature. A Systematic Literature Review (SLR) was employed following a structured review procedure. Relevant empirical studies published between 2021 and 2025 were retrieved from reputable national and international journals. The selected studies were analyzed using qualitative content analysis through identification, categorization, comparison, and thematic synthesis of the findings. The review revealed that Student-Centered Learning consistently improves scientific writing competence by promoting inquiry, collaboration, critical reflection, and evidence-based argumentation. Furthermore, SCL enhances broader dimensions of academic literacy, including academic reading and writing, critical thinking, scientific reasoning, communication skills, and learner autonomy. Among the pedagogical strategies identified, Inquiry-Based Learning, Project-Based Learning, collaborative writing with peer feedback, and technology-enhanced learning demonstrated the strongest and most consistent positive outcomes. These findings suggest that Student-Centered Learning provides an integrated pedagogical framework that transforms scientific writing into an active process of knowledge construction while strengthening academic literacy. Consequently, this review offers valuable theoretical insights and practical recommendations for educators, curriculum developers, and policymakers seeking to design learner-centered scientific writing programs that effectively prepare students for higher education and lifelong learning.